Evaluation of bone density and its relation with radiographic stage in knee osteoarthritis, 2016-2017 - Anari, Hasan; Enteshari-Moghaddam, Afsaneh; Pourfarzi, Farhad; Safarzadeh, Neda (International Journal of Research in Orthopaedics, 2022)
Background: Osteoarthritis (OA) is the most common arthritis and its incidence is directly related to age. According to the related research in the last 30 years, a relationship is reported between severity of osteoarthritis and bone density. The aim of this study was to investigate the bone density and its relation with radiographic stage in knee OA. Methods: In this descriptive cross-sectional study, 123 patients with knee OA diagnosis who referred to rheumatology clinic at Imam Khomeini hospital in Ardabil, were selected to participate in our study. Age, sex, weight, height and other variables were collected and analyzed with SPSS version 21. Results: A significant correlation was found between T-score and age of the patients (r=-0.38, p=0.001). A significant correlation was found between T-score and BMI. The correlation of T-score and radiographic stage of patients with osteoarthritis was indirect and non-significant (r=-0.22, p=0.06). Multivariate regression models showed that among variables, only two variables BMI and age had significant relation with T-score. Conclusions: Results showed that the relation between radiographic stage and T-score was significant and BMI and age had a significant effect on T- score.